Exergoeconomic analysis of a solar-powered/fuel assisted Rankine cycle for power generation. (August 2015) - Cavalcanti, Eduardo J.C.; Motta, Henrique Pereira
Abstract: A Rankine System assisted for solar radiation and fuel combustion which produces 57 kW electrical power are evaluated from exergoeconomic point of view. The Parabolic trough collector efficiency has been performed to investigate its effect as heat source. The exergoeconomic parameters as the relative cost difference and the exergoeconomic factor for each component are evaluated. The analysis is based on the SPECO (Specific Exergy Costing) approach. The simulation of system on March, June, September and December 21st from 7 am to 4 pm for Natal/Brazil using real data was carried out. The results reveal the daily average values of collector efficiencies, ratio of the useful solar energy, electricity produced, the specific cost per exergy unit of the produced electricity and others heat rates. The system is advantageous for higher solar radiation. The outcome of the analysis can be useful in design, optimization of operating parameters and help to take decision of investment. Highlights: As the solar irradiation decreases, the electricity cost per exergy unit increases. The cost rate is high at collector field due to higher purchase cost. The system is advantageous when the solar radiation is high. Further aspect as environmental impact is important.